ДВУХІНВЕРТОРНАЯ ФОТОПРЕОБРАЗОВАТЕЛЬНАЯ СИСТЕМА, РЕГУЛЬОВАНА НА БАЗІ МОДІФІЦІРОВАННОЙ СХЕМИ ВЕКТОРНОЇ МОДУЛЯЦІЇ - Олещук, В.; Єрмуратський, В. (Інститут електродинаміки НАН України, Київ, 2020)
Algorithms of synchronous one-stage modulation have been modified and disseminated for adjustment of two two-level inverters of transformer-based photovoltaic installation with specific double-delta configuration of inverter-side windings of power transformer. Modified algorithms of synchronous space-vector modulation, applied for control of inverters of PV system with specialized connection of windings of power transformer, assure improved spectral composition of winding voltages of transformer, characterized by the lacking in its spectra of even harmonics and undesirable subharmonics for any control modes and regimes of operation of system. References 9, figures 6, table 1.